A poeta e o cronista: as colunas femininas de Alfonsina Storni - Jaquier, Andrezza (2023)
This dissertation presents a study on Alfonsina Storni's female columns published in the Buenos Aires press between 1919 and 1921. In the first column, Feminidades/ Vida Femenina, published in La Nota magazine, the poet Alfonsina Storni signed. In the second, Bocetos Femeninos, published in the newspaper La Nación, the columnist Tao Lao signed. From a critical and multiple theoretical perspective that considers gender relations and criticism as the main thread, this study seeks to understand Alfonsina Storni's writing in female columns, a marketing space targeted at wives, mothers, and consumers: how she wrote and what she put at stake in such specific spaces, what and how Alfonsina produced within and even with these limitations. Unlike the purely negative view of the ideological, sexist, and marketing limitations of female columns, this study reads the limits as a possibility for other inscriptions. Therefore, it investigates first the general and particular context of Alfonsina Storni, the representation and space of the woman writer in Argentine society at the beginning of the twentieth century, the specific literary trajectory, and the location and construction of female columns in the Buenos Aires press. In the second chapter, the study focuses on La Nota magazine and the female columns published by Alfonsina Storni, investigating the strategies of representation of being a woman in modernity. In the third, the study explores Alfonsina Storni's transition to La Nación newspaper, where the signature of Tao Lao is seen, and the dilution of gender stereotypes. Reflecting on the construction of the name and gender performance, the study aims to understand the literary and discursive work in the construction of Tao Lao: he is not just a mask, but a persona with a voice (specifically of a columnist) created for the female section.